(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Yakovenko O. I. Implementation of a competent approach to the higher economic education system. The author of the following article takes into consideration inadequate implementation competent approach in higher education system of Ukraine, stated its methodological shortcomings and offer an initial algorithm for improving the implementation of this approach.